The Role of Islamic Religious Education on Juvenile Delinquency Behavior In Pajam Village - Ice Swarmi swarmi; Farhan; Wulandari (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
Juvenile delinquency is a growing social issue that has become a serious concern across various sectors of society. Deviant behaviors such as gang fights, drug abuse, promiscuity, and even criminal acts are often committed by adolescents experiencing an identity crisis and a lack of moral control. In this context, Islamic Religious Education plays a strategic role in shaping the character and behavior of youth in accordance with religious teachings. This study aims to examine the extent of the influence and contribution of Islamic Religious Education on juvenile delinquent behavior. The research adopts a qualitative approach, with data collection techniques including observation, interviews, and document analysis conducted in secondary school environments. The findings indicate that effectively implemented Islamic Religious Education delivered through contextual approaches and supported by exemplary teacher conduct can instill strong moral and spiritual values in adolescents. A deeper understanding of Islamic teachings, such as the importance of noble character, responsibility, and avoiding prohibited acts, has proven to reduce the tendency toward deviant behavior. Furthermore, support from family and the surrounding community also plays a crucial role in reinforcing the impact of religious education. In conclusion, Islamic Religious Education holds a vital role in preventing and reducing juvenile delinquency, as well as in shaping morally upright and responsible youth.